Channel Spacing dan Signifikansinya terhadap Performansi Jaringan DWDM dan SCM/WDM Radio over Fiber - Rika Susanti (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2011)
Channel spacing is the important thing in order to determine the network capacity. The smaller channel spacing will give rise to the higher capacity. Moreover, the channel spacing is needed to avoid Optical Bit Interference. In this paper, minimum channel spacing obtained was 0.2 nm which generate the BER smaller than 10-12, so that it meets the International Telecommunication Union requirement. The DWDM network model could be implemented with good performance up to 100 km of optical fiber (without amplifier), whereas the SCM/WDM network model up to 90 km (without amplifier).   Keywords: Channel Spacing, DWDM, SCM/WDM, Radio over Fiber